Image and graphics. 10th International Conference, ICIG 2019, Beijing, China, August 23-25, 2019 : Proceedings /: 10th International Conference, ICIG 2019, Beijing, China, August 23-25, 2019 : Proceedings. Part III : ([2019]) - Unknown
No abstract available